Hookah Smoking and Facilitators/Barriers to Lounge Use among Students at a US University - Kassem, Nada O. F. (Am J Health Behav, 2015)
OBJECTIVE: To examine hookah tobacco use, hookah lounge attendance, and facilitators and barriers to hookah lounge attendance. METHODS: A cross-sectional Web-based survey of a random sample of 1332 undergraduate students (Mean Age = 21.2 years) attending a United States university. RESULTS: The majority of respondents (72.8%) had ever smoked hookah tobacco, and 28% of those had ever smoked during adolescence. The majority of ever hookah smokers (81.5%) and a portion of never hookah smokers (20%) had ever been to a hookah lounge. The adjusted odds of ever visiting a hookah lounge were 2.1 times higher among participants who reported that the closest hookah lounge to the university was < 5 miles away than those who reported that the closest hookah lounge was ≥ 5 miles away. Facilitators of visiting hookah lounges included friends and close proximity of hookah lounges to campus; barriers included cost of smoking hookah, crowded lounges, and having to be 18 years old. CONCLUSION: Youth are vulnerable to experimenting with hookah tobacco smoking. Hookah lounges provide patrons the opportunity to smoke hookah tobacco with smoker and non-smoker friends in entertaining settings. Our findings suggest that zoning laws and anti-hookah smoking legislation may help curb hookah uptake by prohibiting hookah lounges from opening in close proximity to universities, reducing the density of hookah lounges in cities, and raising the admission age for hookah lounges to 21 years.